A Prospective, Single Blind, Crossover, Clinical Trial to Assess the Outcomes of Computer-Engineered Complete Dentures from Impressions and Intra-Oral Scans of the Edentulous Arches: A Pilot Study - O'Donoghue, Gabrielle (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2023)
Computer-engineered complete dentures (CECDs) have documented advantages over conventionally fabricated complete dentures for the clinician, technician, and patient. Intra-oral scanning (IOS) of the edentulous arches is possible, but the evidence for its application as the definitive impression technique within CECD protocols is limited to technique articles and case reports. A pilot clinical trial with five participants was conducted to investigate and compare the clinical outcomes and patient-related outcomes of CECDs made from intra-oral scans of the edentulous arches to CECDs made from conventional vinylpolysiloxane impressions. A prospective, blinded, crossover design was implemented. Two sets of CECDs were designed using computer-aided design software (Ivoclar Digital Denture® System, Ivoclar Vivadent AG, Schaan, Liechtenstein), with the denture bases determined by the respective impression technique. The CECDs were milled in monolithic polychromatic polymethylmethacrylate (Ivotion™, Ivoclar Vivadent AG, Schaan, Liechtenstein) through computer-aided manufacturing. One set of CECDs were fitted and their clinical outcomes and acceptability were assessed by two independent, blinded prosthodontists. The CECDs were worn by the participant for one month, and patient satisfaction surveys were completed at week one and week four. The participant's existing complete dentures were returned for a washout period of one month before the process was repeated with the second set of CECDs. Participant preference for the impression technique and set of CECDs was determined at the end of the study period. The results indicated that the application of IOS of the edentulous arches was feasible within the chosen CECD system. There were no differences found between the CECDs with respect to their clinical outcomes including fit, function, aesthetics, occlusion, and overall score. The participants were significantly more satisfied with all dentures after one month of wear compared to at one week. No significant differences were found in patient satisfaction between impression-based and scan-based CECDs. A participant preference towards IOS as an impression modality and towards the scan-based CECDs were found. Limitations of this study included low participant numbers. The null hypotheses could not be rejected because the clinical and patient-related outcomes of monolithic milled CECDs fabricated from intra-oral scans of the edentulous arches were similar to those of monolithic milled CECDs fabricated from conventional impressions. Future studies should include a greater number of participants and stratify the participants according to personality type and edentulous arch morphology.
APPROVED
Keywords: Intra-Oral Scanning; Computer-Engineered Complete Dentures; Digital Dentures; Edentulous Arches; Pilot Trial; Clinical Study